2019
DOI: 10.21203/rs.2.16519/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heart rate and heart rate variability comparison between postural orthostatic tachycardia syndrome versus healthy participants; a systematic review and meta-analysis.

Abstract: Background: A number of published literature has reported that, physiologically, heart rate variability (HRV) in patients with postural orthostatic tachycardia syndrome (POTS) to be greatly confounded by age, sex, race, physical fitness, and circadian rhythm. The purpose of this study was to compare between POTS patients versus healthy participants, in terms of heart rate (HR) and HRV after Head-Up tilt test (HUTT), by systematic review and meta-analysis of available published literature. Methods: MEDLINE (usi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…Characteristics of the participants were described in Table 1. Median average for age was 48 [12] years for patients with long COVID-19 with fatigue, 39 [10] years for patients with long COVID-19 without fatigue and 43 [9] years for the control group. Few patients of our study group presented comorbidities, only 3 patients with hypertension for long COVID-19 groups and one patient for control group, and only one patient with diabetes in long COVID-19 groups.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Characteristics of the participants were described in Table 1. Median average for age was 48 [12] years for patients with long COVID-19 with fatigue, 39 [10] years for patients with long COVID-19 without fatigue and 43 [9] years for the control group. Few patients of our study group presented comorbidities, only 3 patients with hypertension for long COVID-19 groups and one patient for control group, and only one patient with diabetes in long COVID-19 groups.…”
Section: Resultsmentioning
confidence: 98%
“…HRV is mainly related to emotional, social, cognitive and health levels 11 . HRV is the main marker of the modulation of the sympathetic and parasympathetic branches of the ANS, and thus, of dysautonomia 12 . The low-frequency band reflects the modulation of sympathetic and parasympathetic branches on the heart 13 and has been considered as an index of the sympathovagal imbalance 14 .…”
mentioning
confidence: 99%
“…We observed that HRV, reflected by the NOL index, was significant different in post-COVID-19 participants with fatigue compared to control participants. HRV is one of the main marker of dysautonomia 12 . Some etiologies may explain dysautonomia in post-COVID-19 patients including hypoxia, neurotropism and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Ранее выполненные исследования свидетельствуют об информативности показателей состояния ВНС в определении дизрегуляционной патологии, которые получают посредством анализа ВРС. Определено, что у работающих с ночными сменами регистрируются изменения временных и спектральных показателей ВРС в покое [24,29,30], которые объясняют комплексным влиянием измененной циркадной ритмичности, изменениями времени и продолжительности сна [9,29,[31][32][33]. В нашем исследовании получены данные, подтверждающие статистически значимые изменения основных показателей у работников этой категории, которые выражаются в снижении общей мощности регуляции (ТР, SDNN) и парасимпатического звена (HF, pNN50).…”
Section: Discussionunclassified
“…Так, в мета-анализе J. Swai и соавт. [33], в котором объединены результаты 20 исследований ВРС с ортостатической пробой, включивших 717 пациентов с синдромом постуральной ортостатической тахикардии и 641 здорового участника, анализировали возраст, коморбидные состояния и другие факторы, потенциально связанные с изменениями ВРС, но не фактор сменной ночной работы. В исследовании N. M. Monteze и соавт.…”
Section: Discussionunclassified